2002
DOI: 10.1007/s00418-002-0475-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple nicotinic acetylcholine receptor α-subunits are expressed in the arterial system of the rat

Abstract: Neuronal nicotinic acetylcholine receptors (nAChRs) are hetero-and homopentamers built up by nine different α-subunits and three different β-subunits. The subtype composition within the receptor determines ligand specificity, affinity and cation permeability. In this study we focused on the distribution of the ligand binding α-subunits in the rat arterial system by means of RT-PCR and immunohistochemistry. Subtypes α3, α5, α7 and α10 were found to be expressed by endothelial cells, suggesting that they are equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…2). Vascular smooth muscle cells are known to express nicotinic acetylcholine receptors (Bruggmann et al, 2002, 2003); however, to our knowledge, this is the first demonstration of the localization of nicotinic acetylcholine receptors at podosomes and podosome rosettes and the first report of nicotinic acetylcholine receptor-mediated formation of podosome rosettes in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 81%
“…2). Vascular smooth muscle cells are known to express nicotinic acetylcholine receptors (Bruggmann et al, 2002, 2003); however, to our knowledge, this is the first demonstration of the localization of nicotinic acetylcholine receptors at podosomes and podosome rosettes and the first report of nicotinic acetylcholine receptor-mediated formation of podosome rosettes in vascular smooth muscle cells.…”
Section: Discussionmentioning
confidence: 81%
“…Although cigarette smoke is a complex mixture, nicotine is considered the main toxic and addictive compound of tobacco and a clinical risk factor for atherosclerosis (24). Nicotine activates a family of receptors involved in endogenous cholinergic signaling pathways (4). Two different types of nicotinic acetylcholine receptors are distinguished.…”
mentioning
confidence: 99%
“…The presence of neuronal nicotinic acetylcholine receptors (nAChRs) at locations unrelated to synaptic activity supports the hypothesis that acetylcholine may have cellular functions mediated by nicotinic receptors (5). nAChRs are present on nerve fibers innervating blood vessels, and there is growing evidence for an nAChR-mediated direct effect of nicotine on the arterial wall (46). The presence of nAChRs in a variety of non-neuronal cells, unrelated to synaptic activity, suggests that nicotine causes some of its toxic effects in the respiratory and cardiovascular systems by binding to nAChRs in these organs (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since after inhibiting the muscarinic receptors with 4-DAMP the remaining site of action of carbachol would be with nicotinic receptors, it is plausible to hypothesize that nicotinic receptors might modulate purinergic receptor desensitization. Recently, several nicotinic receptor subtypes have been described in vascular smooth muscle [6]. Although we have not provided any direct evidence of putative interaction between nicotinic and purinergic receptors in the bladder, other studies have shown that nicotinic and purinergic receptors can negatively interact with each other in the neural cells of sympathetic or enteric ganglia [2, 21, 33].…”
Section: Discussionmentioning
confidence: 56%